2003
DOI: 10.1046/j.1442-9993.2003.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of grazing and burning on spider assemblages in dry eucalypt forests of north‐eastern New South Wales, Australia

Abstract: In the dry eucalypt forests of north-eastern New South Wales, Australia, cattle grazing occurs at low intensities and is accompanied by frequent low-intensity burning. This study investigated the combined effects of this management practice on the ground-dwelling and arboreal (low vegetation) spider assemblages. Spiders were sampled at 49 sites representing a range of grazing intensities, using pitfall trapping, litter extraction and sweep sampling. A total of 237 spider morphospecies from 37 families were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
(69 reference statements)
2
15
2
1
Order By: Relevance
“…Based on these findings the suitability of spiders to reflect differences in habitat structure as found for example by Harris et al (2003), Bonte et al (2006), Foord et al (2008) and Blaum et al (2009) could be clearly confirmed. Also, spiders are a suitable model group to assess differences in habitat quality since each habitat type was characterised by certain species that showed clear responses to environmental shifts within the habitat structure.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Based on these findings the suitability of spiders to reflect differences in habitat structure as found for example by Harris et al (2003), Bonte et al (2006), Foord et al (2008) and Blaum et al (2009) could be clearly confirmed. Also, spiders are a suitable model group to assess differences in habitat quality since each habitat type was characterised by certain species that showed clear responses to environmental shifts within the habitat structure.…”
Section: Discussionmentioning
confidence: 67%
“…Spiders are useful indicators of the ecological status of biotic communities, and of changes in habitat and landscape structure (Hsieh et al 2003;Warui et al 2005;Foord et al 2008;Horvath et al 2009). Furthermore, they are helpful to monitor habitat management and restoration success (Dennis et al 2001;Harris et al 2003;Perner and Malt 2003;Petillon et al 2005;Grill et al 2005;Huber et al 2007). While various studies have analysed the diversity and community structure of spiders in inland sand ecosystems (Finch 1997;Merkens 2002;Buchholz 2008;Buchholz and Hartmann 2008), the relations of spider assemblages with local habitat structure have so far been insufficiently documented.…”
Section: Introductionmentioning
confidence: 98%
“…Moderate grazing intensity results in higher vegetation, which is usually vertically more structured and it increases the spider richness. Dennis et al (2001) and Harris et al (2003) also pointed out that rich vertical structure and the height of vegetation facilitate the spider richness. Intense grazing decreases the spider diversity, and it increases the abundance of disturbance-tolerant species (Gibson et al, 1992a;Bell et al, 2001).…”
Section: Effects Of Grazingmentioning
confidence: 99%
“…Impacts and management actions on forest systems range from various types of timber harvesting, wildfire, prescribed burning, attack by insect pests, and forest fragmentation (e.g., Docherty and Leather, 1997; Harris et al, 2003;Abbott et al, 2003;Brennan et al, 2006;Chen and Tso, 2004;Baldissera et al, 2008). The conversion of native forests into tree plantations can potentially affect the distribution and occurrence of spiders.…”
Section: Introductionmentioning
confidence: 99%